A new analytical approximation to the extended Brinkman equation - Maußner, Johannes; Pietschak, Alexander; Freund, Hannsjörg (Chemical Engineering Science, 2017)
Keywords: Reactor optimization; Heat transfer; Radial flow profile; Fixed bed reactors; Brinkman equation

A new heat transfer correlation suited for the design of fixed-bed reactors via numerical optimization - Pietschak, Alexander; Dixon, Anthony G.; Freund, Hannsjörg (Chemical Engineering Science, 2020)
A new correlation to account for the radial heat transfer in fixed-beds modeled via a 2D pseudo-homogeneous approach is presented in this contribution. Compared to state-of-the-art heat transfer correlations, no points of discontinuity are included in the definition of the new heat transfer correlation. This enables a direct application of gradient-based solution algorithms for the reactor design via numerical optimization. The presented heat transfer correlation is based on individually considering the influence of the radial velocity profile and radial bed voidage profile in the fixed-bed on the heat transfer. The predictive performance of the presented heat transfer correlation is benchmarked against the state-of-the-art heat transfer correlation proposed by Winterberg et al. for both, spherical and cylindrical shaped particles, based on an evaluation of a broad measurement data basis from literature heat transfer experiments.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Catalytic fixed-bed; Heat transfer; Numerical optimization; Reactor design; Transport phenomena

Comparative evaluation of heat transfer correlations with different fluid property considerations for fixed-bed reactor modeling - Pietschak, Alexander; Maußner, Johannes; Dixon, Anthony G.; Freund, Hannsjörg (International Journal of Heat and Mass Transfer, 2020)
Catalytic fixed-bed reactors are well established and frequently used in the chemical industry. Full-scale catalytic fixed-bed reactors are commonly described via pseudo-homogeneous continuum models. The heat transfer is accounted for by correlations that have been predominately fitted under the assumption of constant fluid properties. As a result of chemical reactions taking place, the fluid composition and the temperature in the fixed-bed depend on the spatial position. The resulting system specific non-uniformity of the fluid properties should be taken into account during modeling. The effect of different approaches to consider the fluid properties in the bed on the predictive performance of selected heat transfer correlations is evaluated on a broad range of experimental heat transfer data obtained from the literature. Correlations from both the αw- and the λr(r)-heat transfer models were selected. Although the selected correlations have been fitted under the assumption of constant fluid properties, the predictive performance was improved for all correlations if radial and axial variations of the fluid properties were taken into account. The impact on the resulting temperature field is illustrated based on a case study. In addition, the predictive performances of the selected heat transfer correlations are compared to one another over a broad range of tube-to-particle diameter ratios and Reynolds numbers. A clear superiority of the λr(r)-correlation proposed by Winterberg et al. was identified.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Catalytic fixed-bed; Fixed-bed reactor simulation; Fluid properties; Heat transfer; Model evaluation; Pseudo-homogeneous models

Tailored catalyst pellet specification for improved fixed-bed transport characteristics: A shortcut method for the model-based reactor design - Pietschak, Alexander; Kaiser, Markus; Freund, Hannsjörg (Chemical Engineering Research & Design, 2018)
tTo improve the transport characteristics of a catalytic fixed-bed via optimal design of catalystpellet specifications such as the pellet diameter it is necessary to account for all physico-chemical phenomena influenced by the pellet. For the approximative description of thetransport phenomena on the catalyst pellet scale a new shortcut method is developed inthis work. It enables a generalized and system independent treatment of the aforementionedprocesses and can be applied to arbitrary reaction networks and reaction kinetic models.Based on linearization and decoupling of the pellet balance equations the method yields ananalytical solution. This allows for model-based design of the reactor-catalyst system viadynamic optimization at reduced computational costs as the use of complex heterogeneousmodels is avoided. In order to ensure accurate predictions of the method, regions with highcatalyst utilization are targeted. To indicate the potential of improved bed transport characteristics, the shortcut method isapplied to the reactor-catalyst system for ethylene oxide synthesis. The system is optimizedin terms of reducing the pressure drop while meeting other reactor performance constraints.The pressure drop could be reduced by more than 60%. The shortcut method is validatedusing a rigorous stand-alone model of the catalyst pellet.
Keywords: Reactor optimization; Thiele modulus; Fixed-bed reactors; Process intensification; Catalyst pellet design